Effects of rainfall intensity and mitigation measures on slope stability: a case study of Shatianpo landslide in Yunyang county, Chongqing City, Southwest China - Zheng, Xiangsheng; Zhang, Yan; Meng, Kai; Hu, Yitao; Zou, Minglang; Xiang, Haiquan; Luo, Yu (Frontiers in Earth Science, 2025)
The frequency and magnitude of landslide disasters triggered by heavy rainfall are on the rise. Investigating the mechanisms behind landslide formation and assessing their stability is essential for enhancing our capabilities in the prevention and control of such disasters. This paper analyzes and summarizes the fundamental characteristics and formation mechanisms of the Shatianpo landslide. Using Geostudio software, we assessed the stability of the landslide under varying rainfall intensities, different support methods, and the combined effects of earthquakes and rainfall. The results indicate that the slope range is unstable under high rainfall intensities, whereas it is lack of stable or basically stable under low rainfall intensities. The stability coefficient of the slope can be improved by 0.3–0.5 with the implementation of anti-slide piles, and its condition can shift from unstable to stable during heavy rainfall events. Furthermore, the research on various anchor bolt support parameters reveals that optimal slope stabilization is achieved when the anchor bolt length is 15 m, with a spacing of 2.5 m between bolts, an anchorage angle of 25°, and anchor placement situated at the middle and front sections of the landslide. Notably, under identical earthquake intensities, the stability coefficient is greater during short-duration heavy rainfall compared to long-duration weak rainfall. This study provides valuable insights for the stability analysis and selection of support measures for similar slopes in the region.